Assessing the role of regional educational integration policies in fostering university-industry-research innovation: Evidence from China - Qi Chen; Jiawen Zhou (PLoS ONE, 2025)
Regional integration is a key strategy for enhancing competitiveness and promoting innovation, and regional education integration has become an important part of regional integration. At the same time, university-industry-research (UIR) collaborative innovation is also a key link in building a national innovation system. This study empirically analyzes the impact of China’s Yangtze River Delta regional education integration policy on UIR innovation cooperation by using a difference in difference model. The results show that the regional education integration policy significantly promotes UIR innovation cooperation, especially in Zhejiang and Jiangsu, which have a stronger economic base and richer educational resources. In addition, the policy has an extraordinarily prominent role in promoting invention patents with higher innovation intensity. The mechanism analysis finds that human capital, economic capital, government support and social stability play an important mediating role. Finally, policy recommendations are made based on the empirical results.